Angiotensin II type 1 receptor antibodies as a contributor to microvascular inflammation in kidney transplant recipients: insights from statistical and artificial intelligence based approaches - Mizera, Jakub; Donizy, Piotr; Halon, Agnieszka; Janczak, Dariusz; Kepinska, Marta; Pondel, Maciej; Banasik, Miroslaw (Frontiers in Immunology, 2025)
IntroductionIn recent years, advancements in the classification of renal allograft pathology have led to a notable increase in the diagnosis of antibody-mediated rejection (ABMR). Particular attention has been given to microvascular inflammation (MVI), a subcategory of ABMR that was reappraised in the Banff 2022 classification. Recognizing a significant discrepancy between the number of patients testing positive for donor-specific anti-HLA antibodies (DSAs) and those clinically diagnosed with ABMR, this study aims to explore the potential role of non-HLA antibodies, specifically, antibodies against the angiotensin II type 1 receptor (AT1R), in the development of MVI.Material and methodsA retrospective analysis was performed on clinical and pathological data from 167 kidney transplant recipients. MVI was diagnosed histologically based on biopsy findings, specifically a glomerulitis score (g) > 0 and/or peritubular capillaritis (ptc) > 0. Based on these criteria, two patient cohorts were identified: 88 patients without MVI and 79 patients with MVI. Statistical analyses were conducted using appropriate methods, including chi-square tests, Student’s t-tests, and Mann–Whitney U tests. Additionally, complementary analyses utilizing artificial intelligence techniques such as correlation analysis, logistic regression and association rule mining were applied to maximize insights from the dataset.ResultsPatients with MVI demonstrated a statistically significantly higher prevalence of AT1R antibodies compared to those without MVI. The finding was confirmed by both traditional statistical methods and artificial intelligence analysis. Furthermore, the MVI-positive cohort exhibited a higher frequency of C4d positivity compared to patients without MVI.ConclusionsThe presence of AT1R antibodies may be associated with the development of microvascular inflammation, potentially contributing to allograft injury in a subset of cases of kidney transplant recipients. High AT1R abs titers (>12 U/ml) were particularly important, while lower levels did not show the meaningful association. These findings underscore the importance of broadening immunologic surveillance beyond conventional anti-HLA antibody screening.